2015
DOI: 10.1016/j.jag.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing bi-temporal patterns of land surface temperature using landscape metrics based on sub-pixel classifications from Landsat TM/ETM+

Abstract: 16Landscape patterns in a region have different sizes, shapes and spatial arrangements, 17 which contribute to the spatial heterogeneity of the landscape and are linked to the distinct 18 behavior of thermal environments. There is a lack of research generating landscape metrics 19 from discretized percent impervious surface area data (ISA), which can be used as an 20 indicator of urban spatial structure and level of development, and quantitatively characterizing 21 the spatial patterns of landscapes and land s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Different LULC types had different specific heat capacities, and vegetation was transferred to built-up land, which increased LST [69]. This is consistent with the results of previous studies [70], indicating that ISA changes have a large impact on the spatial distribution of LST.…”
Section: Discussionsupporting
confidence: 90%
“…Different LULC types had different specific heat capacities, and vegetation was transferred to built-up land, which increased LST [69]. This is consistent with the results of previous studies [70], indicating that ISA changes have a large impact on the spatial distribution of LST.…”
Section: Discussionsupporting
confidence: 90%
“…From this data, it can be concluded that the LST significantly rises when other types of LULC are converted to ISA, and that it is relatively stable in areas where the ISA shows No Change, but in regions where the ISA decreased, the LST showed a significant negative trend. This is consistent with the results of previous studies [40,41], further indicating that ISA regional changes have a large impact on the spatial distribution of LST.…”
Section: Figuresupporting
confidence: 93%
“…In addition to prevailing meteorological conditions across local-and meso-scales, urban fabric properties play the key role in formation of the UHI effect via complicated processes such as biophysical features of the land surfaces, building layout and wind corridor, landscape heterogeneity, energy consumption and anthropogenic heat emission [12,[39][40][41][42][43][44][45]. In this study, we presented the differential thermal effect of urban fabric properties, i.e., LST, UHI intensity and BBFD associated with varying land surfaces at UFZ level.…”
Section: Implications For Mitigating the Uhi Effectmentioning
confidence: 99%